Peningkatan Hasil Belajar Siswa Slow Learner Dengan Menggunakan Alat Peraga IPA Kelas III SDN Cibunar - Lintang Febriliani CA (Jurnal Ilmiah Wahana Pendidikan, 2022)
The low learning outcomes of class III students at SDN Cibunar Balapulang are due to the lack of direct student involvement in the learning process. To overcome this problem, a class action research (CAR) was conducted through the use of science teaching aids. The purpose of this study was to improve student learning outcomes by using science teaching aids for class III at SDN Cibunar. The research subjects consisted of 21 students. The source of the research data was obtained from qualitative data in the form of data from observations of teacher and student activities as well as quantitative data in the form of test data on student learning outcomes. The results of the first cycle of research obtained students who completed individually as many as 8 students out of 21 students with classical completeness of 36% and classical absorption of 63%. While the results of the second cycle research increased with the number of students who completed individually as many as 16 students out of 21 students who took part in learning with a classical completeness percentage of 82% with a classical absorption of 85%. Based on the results of this study, learning using natural science tools can improve student learning outcomes in class III SDN Cibunar.